Mother to child trasmission of human immunodeficiency virus: how to teduce the tisk - Azevedo, Kátia M. L. (Brazilian Journal of Sexually Transmitted Diseases, 2001)
After 20 years. lhe human immunodeficiency virus (HIV) infection epidemie has exibited many changes. Most HIV infections in children have becn transmitted perinatally. Many of the factors associated with transmission are already known, like the imcrventions 10 reduce the risk of mother-10-child transmssion of HIV. lt is importam tha1 heahh profissionais bc up-10-date with the prevenlion of HIV vertical lransmission, the main way 10 control 1he expansion of the epidemie in children. This paper reports 1he data from lhe epidemie in Brazil. the factors that iníluence the mother-10-child transmission of HIV infection and lhe strategies recommended to preveni the infection, including de anti-retrovirals drugs given to lhe pregnant and to the newbom.